Molecular characterization of exonic rearrangements and frame shifts in the dystrophin gene in Duchenne muscular dystrophy patients in a Saudi community - Elhawary, Nasser A.; Jiffri, Essam H.; Jambi, Samira; Mufti, Ahmad H.; Dannoun, Anas; Kordi, Hassan; Khogeer, Asim; Jiffri, Osama H.; Elhawary, Abdelrahman N.; Tayeb, Mohammed T. (Human genomics, 2018)
In individuals with Duchenne muscular dystrophy (DMD), exon skipping treatment to restore a wild-type phenotype or correct the frame shift of the mRNA transcript of the dystrophin (DMD) gene are mutation-specific. To explore the molecular characterization of DMD rearrangements and predict the reading frame, we simultaneously screened all 79 DMD gene exons of 45 unrelated male DMD patients using a multiplex ligation-dependent probe amplification (MLPA) assay for deletion/duplication patterns. Multiplex PCR was used to confirm single deletions detected by the MLPA. There was an obvious diagnostic delay, with an extremely statistically significant difference between the age at initial symptoms and the age of clinical evaluation of DMD cases (t value, 10.3; 95% confidence interval 5.95-8.80, P < 0.0001); the mean difference between the two groups was 7.4 years. Overall, we identified 147 intragenic rearrangements: 46.3% deletions and 53.7% duplications. Most of the deletions (92.5%) were between exons 44 and 56, with exon 50 being the most frequently involved (19.1%). Eight new rearrangements, including a mixed deletion/duplication and double duplications, were linked to seven cases with DMD. Of all the cases, 17.8% had duplications with no hot spots. In addition, confirmation of the reading frame hypothesis helped account for new DMD rearrangements in this study. We found that 81% of our Saudi patients would potentially benefit from exon skipping, of which 42.9% had a mutation amenable to skipping of exon 51. Our study could generate considerable data on mutational rearrangements that may promote future experimental therapies in Saudi Arabia.